1 & 2 Thessalonians - Phillips, Richard D. (Richard Davis), 1960- (Phillipsburg : P & R Pub., 2015)
Years before writing Romans or Ephesians, Paul sent a pair of letters to a new church in Thessalonica. Three concerns governed Paul's teaching in these letters: What makes a healthy church? How should we view God's Word? What does a Christian life look like? Richard D. Phillips's commentary considers these foundational issues in a scholarly, pastoral, and practical manner and also explores Paul's end-times teaching--the clearest found in the New Testament. Through these studies, readers will find a refreshingly clear biblical summary of what will happen before, during, and after the Second Coming. Just as importantly, by touring Paul's singular teaching in 1 and 2 Thessalonians, readers will recover a joyful anticipation of Christ's return and receive hope for life in a challenging world. -- Amazon.com
Thessalonians: In light of Christ's coming. Growing in faith : 2 Thessalonians 1:1-4 -- God's righteous judgment : 2 Thessalonians 1:5-8 -- The biblical doctrine of hell : 2 Thessalonians 1:8-9 -- Glorified in his saints : 2 Thessalonians 1:10-12 -- End-times dangers : 2 Thessalonians 2:1-3 -- The man of lawlessness : 2 Thessalonians 2:3-10 -- The great apostasy : 2 Thessalonians 2:3, 9-12 -- The mystery of lawlessness : 2 Thessalonians 2:5-8 -- To obtain the glory : 2 Thessalonians 2:13-15 -- Encouraged and established : 2 Thessalonians 2:16-17 -- Praying with confidence : 2 Thessalonians 3:1-5 -- Willing to work : 2 Thessalonians 3:6-15 -- With his own hand : 2 Thessalonians 3:16-18.
Includes bibliographical references (pages 413-414) and index.
Keywords: Bible. -- Commentaries